BEBAN DAYA GENZET DI KERETA K3 (EKONOMI) ATAS PEMASANGAN AC SPLIT (AC RUMAH) (Jurnal Penelitian Transportasi Darat, 2015)
ABSTRACTInstallation of split air conditioners on trains applied by PT. KAI toward two types of passenger train, i.e. the class train 2 (business) and class train 3 (economy). The purpose of the installation of the AC is to improve services and comfort the passengers. In 2013, PT KAI has authorized installing split air conditioners throughout the long-distance trains in Indonesia for grade 2 and 3. However what’s interesting is the installation of split AC class 3 on the train applied 6 units air conditioner on each train, is it possible for train generator to accomodate the power used to cool down the room air inside the train. The method in calculating capacity of split air conditioners which amounted to 6 unit on ecah train into account KVA power after a series of split air conditioners installed. From the analysis it was found that the air conditioning capacity is smaller than the power load that must be accepted by the AC hence the AC needs to work harder cooling the space. Thus from the calculation of the percentage of effectiveness generator, known that is not been used optimally, since the percentage of effectiveness reached an average 35%.ABSTRAKPemasangan AC split pada kereta diterapkan oleh PT. Kereta Api Indonesia (Persero)/PT. KAI pada dua jenis kereta api penumpang, yaitu kereta api kelas 2 (bisnis) dan kereta api kelas 3 (ekonomi). Tujuan pemasangan AC ialah untuk meningkatkan pelayanan dan kenyamanan kepada penumpang. Pada tahun 2013 PT. KAI telah resmi memasang AC split di seluruh kereta api kelas 2 dan kelas 3 jarak jauh di Indonesia. Namun yang menjadi perhatian adalah pemasangan AC split pada kereta api kelas 3 dengan jumlah 6 unit AC pada tiap kereta api, apakah genzet mampu menampung daya yang digunakan untuk mendinginkan udara didalam kereta api. Metode dalam menghitung kapasitas AC split yang berjumlah 6 unit di tiap-tiap kereta memperhitungkan daya KVA rangkaian setelah dipasang AC split. Dari hasil analisis ditemukan bahwa kapasitas AC lebih kecil dibandingkan dengan beban yang harus diterima oleh AC sehingga AC harus bekerja lebih keras dalam mendinginkan ruang kereta. Kemudian dari perhitungan persentase efektifitas genzet, diketahui bahwa kapasitas genzet belum digunakan dengan optimal, karena persentase efektifitasnya baru mencapai angka rata-rata 35%.